KEHIDUPAN SOSIAL EKONOMI PETANI DI HOLTIKULTURA DI KENAGARIAN SUNGAI NANAM KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK (2001-2012) - Fitria, Yun Roza; NURHUDA, Ahmad; Yulia, Refni (Pendidikan Sejarah, 2013)
ABSTRACT YUN ROZA FITRIA (09020150) Economic Social Life Horticultural Farmers in Kenagarian Nanam River Valley Gumanti Solok District (2001-2012) Education Studies Program History STKIP PGRI Sumbar 2013.This thesis is a study of the socio-economic history by selecting the title of Socio  Economic Life of Farmers Horticultural Society in Kenagarian Nanam River Valley Gumanti Solok District ( 2001-2012 ) . It is interesting to discuss , because the development of horticultural farms can change the economy well. The following research issues : ( a) How do the peoples livelihood Nanam River before the development of horticultural farms , ( b ) What is the impact on the  lives of agricultural horticultural societies in Kenagarian Nanam River Valley  Gumanti Solok district .Skripi writing this using historical research methods consisting of four stages : heuristic, Criticism, Interpretation, and the Historiography of the stage   presentation of the results of a research thesis . 2001 people in Kenagarian Nanam  River Valley Gumanti Solok district began to focus horticulture crops in paddy fields . Prior to the public horticulture crops rely on rice as an economic resource. Transition ketanaman rice paddy crop horticulture occur because it can no longer  meet peoples lives . Agriculture horticulture can improve farmer incomes this can  be seen from the ownership of luxury items such as permanent housing, food,  clothing, educational improvement in Kenagarian Nanam River Valley Gumanti Solok district  Key word: Social, Economic, Farmers, Horticultural